POLA KOMUNIKASI PEMBELAJARAN PADA ANAK DENGAN HAMBATAN PENDENGARAN DI SLB SUKAPURA KOTA BANDUNG - Asri Fitrananda, Charisma; Devi Affandi, Nur Ratih (Ilmu Komunikasi, FISIP Universitas Pasundan, 2024)
Children with hearing impairments experience difficulties in recognizing sounds around them so they usually utter meaningless words. Thus, of course, when writing a sentence they also experience errors in the form of writing meaningless words and sentences. One of the obstacles in providing learning services to children with hearing impairments is the lack of appropriate learning that is applied to them. The lack of innovative media is an obstacle for teachers in SLB. This research uses a qualitative research method with a phenomenological type of research consisting of field observations and in-depth interviews. The informants interviewed by the research team were students, teachers and parents at SLB Sukapura, Bandung City. Using the symbolic interaction theory approach from Herbert Mead, the results of this research found that the language used as a communication medium was BISINDO sign language, because BISINDO is the natural language of children with hearing impairments and they feel they understand better if they use BISINDO. In fact, it is not the child who follows the teacher's language but the teacher who follows the child's language. Not a few other special schools also use SIBI sign language as a learning communication medium because SIBI is considered the standard Indonesian sign language whose language structure is in accordance with Indonesian. But in reality, SIBI was created by the government, which is a hearing person, while sign language is a language belonging to people with hearing impairments, which of course had to be made by hearing impaired people.